MALLOW APPS: Aplikasi Berbasis Android untuk Pencegahan dan Monitoring Gangguan Depresi - Pratiwi Wikaningtyas; Hubbi Nashrullah Muhammad; Dhyan Kusuma Ayuningtyas; Spoudy Lucianus; Maria Ines Wibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Depression is often defined as a mental condition characterized by severe despondency and dejection, typically also with feelings of inadequacy and guilt, often accompanied by a lack of energy and disturbance of appetite and sleep. Its mortality rate is 800 thousand deaths worldwide. This project aims to make a gamified Android-based application to prevent and treat depression titled Mallow apps. The stages of this project were planning, designing, prototyping, usability testing and satisfaction, and publishing. Figma was the primary tool used for designing and prototyping. The prototype’s functionality was measured by success rate and ease of use. User satisfaction was measured by using a SERVQUAL-based questionnaire. Mallow has several features: medication and appointment reminders, drug information, depression self-test, education specifying depression, and a mood board, a collage art therapy. The functionality test showed a success rate of 88.9% and an easiness rating of 4.4 on a scale of one to five in the latest Mallow version. The satisfaction evaluation showed an expectation score of 4.63 and a perception score of 4.42 on a scale from 1 to 5. It is possible to use Mallow Apps for widespread.